Kontroversi Gerakan Fajar Nusantara (GAFATAR) Di Indonesia Dalam Tinjauan Ortodoksi Dan Heterodoksi - Arman (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This article discusses the Fajar Nusantara Movement (GAFATAR), a spiritual movement that emerged in Indonesia in 2015. This movement has attracted public and media attention because of the controversies surrounding its activities and beliefs, especially regarding the dogma of teachings which they believe are heretical, so the movement This was dissolved by the Government in this case the Ministry of Home Affairs. The results of this study show that the pros and cons of religious discourse, in this case the Fajar Nusantara Movement, gave birth to orthodoxy-heterodoxy discourse claims. Discourses that are followed by the majority and supported by the authorities or the government or other authorities are claimed as orthodox discourses, whereas discourses that are only followed by a handful of people, not supported by state authorities or scholars are considered as heterodox discourses, in this study the Fajar Nusantara Movement is considered as heterodox because they are a minority who are not supported by the authorities or the majority of the Muslim community, while the Government is considered orthodox because they are the highest authority holders. However, it should be emphasized that orthodox discourse is not always orthodox and heterodox discourse becomes heterodox forever, it all depends on the conditions of those in power.